The influence of leadership skills on endowment fund sustainability in Oman: a conceptual study / Hazaa Juma Al Bekari and Kamisah Supian - Al Bekari, Hazaa Juma; Supian, Kamisah (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The reality that Endowment Fund is a successful instrument in combating poverty due to its ability to provide vital infrastructure and services for the Islamic community. Unfortunately, the Endowment Fund has been underrated when it comes to its true ability. By misguided emphasis, Endowment investments have been abused and neglected. Under administration and inadequate regulatory action are among the key problems and challenges prevailing in many Muslim societies. Hence, Oman is a nation without equal sustainability of its Endowment Fund However, it has the resources and ability to lead the market. This paper is aiming to explore the connection between leadership skills and the survival of an endowment fund. This paper helps define the leadership models that should be used to support Endowment Fund Sustainability, and how they can work symbiotically. This paper speculates about the use of leadership strategies to support the Endowment Fund in Oman.